Preparation Of Heavy Metal Adsorbent From Microwave Pyrolytic Char Of Sago Wastes - Calidya, Anak Idem (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Preparation of activated carbons from sago wastes were investigated in this study. The raw material of sago wastes was first pyrolysed in a pyrolysis reactor in inert condition for a total of 3 minutes. The samples was subjected with N2 gas for 30 minutes to get an inert environment inside the quartz reactor before exposing the samples to microwave action for at least 3 minutes. The char sample was added with 50 % H2SO4 and 50% Na2SO4 for activation. The adsorption rate has been studied under several parameters like adsorbent dosage, initial concentration, pH and agitation time with three types of heavy metals, which include Lead, Pb(II), Copper, Cu(II) and Chromium, Cr(II). The adsorption parameters influenced on the adsorption rate were analyzed using Langmuir and Freundlich isotherm. The characteristics of the sago waste activated carbon were also investigated by studying the moisture content, ash content, volatile matter content, fixed carbon, surface morphology (SEM) and functional groups (FT-IR). Batch Adsorption test showed that the adsorptions of Pb(II), Cu(II) and Cr(II) metal ion differ for each parameter. According to the evaluation using Langmuir equation, the monolayer adsorption capacity obtained were 0.4464 mg/g, 0.0371 mg/g and 3.5714 mg/g for Pb(II), Cu(II) and Cr(II) respectively.